2021
DOI: 10.13189/ujaf.2021.090427
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Financial Literacy and Financial Inclusion among Women in Indian SHGs

Abstract: The purpose of the study is to analyse the factors contributing to financial literacy and financial inclusion among women of self-help groups (SHGs) of Sisilo village in Balianta block of Bhubaneswar, India. A survey questionnaire was designed and administered to a sample of 100 women respondents in the age group of 18 to 59 years. The survey data were analysed using factorial analysis. Factor extraction was done by the method of principle component analysis. The three factors extracted which influenced financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…F. Hair et al, 2006). The Bartlett’s test of sphericity rejects the null hypothesis of no correlation among the variables ( p < .000), while the Kaiser-Meyer-Ohlin (KMO) measure of sampling adequacy yields a value of .778, indicating that the data are suitable for factor analysis (Mishra et al, 2021).…”
Section: Data and Variablesmentioning
confidence: 99%
“…F. Hair et al, 2006). The Bartlett’s test of sphericity rejects the null hypothesis of no correlation among the variables ( p < .000), while the Kaiser-Meyer-Ohlin (KMO) measure of sampling adequacy yields a value of .778, indicating that the data are suitable for factor analysis (Mishra et al, 2021).…”
Section: Data and Variablesmentioning
confidence: 99%
“…Учеными выявлено, что «уровень толерантности к инвестиционному риску зависит от уровня финансовой грамотности» [5], «финансовые знания способствуют расширению финансовых возможностей людей» [6], «уровень финансовой грамотности населения влияет на курение и потребление ими алкоголя» [7; 8]. Исследования уровня финансовой грамотности и финансовых возможностей женщин различных стран раскрывают «гендерные различия как фактор, препятствующий финансовой грамотности и финансовой доступности» [9], «гендерный разрыв в уровне финансовой грамотности среди подростков» [10], «зависимость между сложностью инвестиционных решений и уровнем финансовой грамотности у представителей разного пола» [11], «более высокий уровень финансовой грамотности у мужчин, но более высокую культуру сбережений у женщин» [12], на основании чего ученые приходят к выводу «о важности разработки программ, предназначенных специально для женщин» [13].…”
Section: обзор литературыunclassified
“…Все респонденты были проинформированы об участии в исследовании. Для проверки гипотезы исследования они были сгруппированы по двум категориям: 1) ведущие -вузы Москвы и Санкт-Петербурга, а также федеральные и национальные исследовательские университеты 9 ; 2) региональные вузы, не имеющие особого статуса 10 . Удельный вес опрошенных студентов ведущих вузов составил 29,7 %, региональных -70,3 %.…”
Section: материалы и методыunclassified
“…The other study in Indian context (Malik et al, 2020) also found household income and expenditures to be significant determinants of credit demand in addition to education and employment. Gender difference along with other socio-economic factors such as access to education, ethnicity, income and lack of trust also hinders women's financial literacy and inclusion (Girón et al, 2021;Mishra et al, 2021). Mindra et al (2017) postulated that women's self-efficacy is a significant factor for women's financial inclusion.…”
Section: Findings From Studies At Household/individual Levelmentioning
confidence: 99%